Analysis of Seismotectonic Parameters and Earthquake Return Periods in The Nias Area (1980-2021): Analisis Parameter Seismotektonik dan Periode Ulang Gempa Bumi di Wilayah Nias Tahun 1980-2021 - Riski Efrina Siregar; Lailatul Husna Lubis; Ratni Sirait; Novita Sari (Departemen Geofisika, FMIPA - Universitas Hasanuddin, Makassar, 2023)
The Nias Islands region is an area prone to earthquakes with a very high level of earthquake activity. One reason is the source of the subduction zone which is in the northwest of the Nias Islands. The aim of this work is to determine the b-value, seismic index, and earthquake return period using probabilistic techniques. For the years 1980 to 2021, the Meteorology, Climatology and Geophysics Agency (BMKG) published data with a magnitude of 3-6.7 and a depth (H) of 10-300 Km. The research results obtained by calculating the highest b-value is 0.791 in South Nias district and the highest a-value is in the South Nias district of 3.97. Calculation of the highest seismicity index with a magnitude of 6.7 in South Nias district with a-value of 7.223191 with an earthquake return period of 14 years.